2000
DOI: 10.1177/089198870001300402
|View full text |Cite
|
Sign up to set email alerts
|

Review of Outcome Measurement Instruments in Alzheimer's Disease Drug Trials: Psychometric Properties of Functional and Quality of Life Scales

Abstract: The psychometric properties of functional and quality of life outcome measures that were used for the purpose of showing changes in antidementia drug trials for Alzheimer's disease are described and critiqued. The seven functional scales reviewed for reliability, validity, and responsiveness to change included the Geriatric Evaluation by Relative's Rating Instrument, the Physical Self-Maintenance Scale, the Instrumental Activities of Daily Living, the Blessed Dementia Scale, Part 1 and its revised version, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
1
29
0
3
Order By: Relevance
“…[112][113][114][115][116] The structure, administration method and target population for each measure are described here and summarised in 89 consists of 31 items covering six domains (positive affect, ability for communication, negative affect/negative action, spontaneity/activity, restlessness and attachment to others). The questionnaire is reported by a proxy (either nursing staff or a family carer).…”
Section: Critical Review Of Measures Of Hrqol In Dementiamentioning
confidence: 99%
“…[112][113][114][115][116] The structure, administration method and target population for each measure are described here and summarised in 89 consists of 31 items covering six domains (positive affect, ability for communication, negative affect/negative action, spontaneity/activity, restlessness and attachment to others). The questionnaire is reported by a proxy (either nursing staff or a family carer).…”
Section: Critical Review Of Measures Of Hrqol In Dementiamentioning
confidence: 99%
“…However, proxy reports may be biased by personal beliefs regarding what constitutes QOL from the perspective of a person who is cognitively intact. Therefore, a scale based on direct observation of behavior and affect might have much to offer if it were sensitive to change [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the perceived difficulties of using everyday technology among people with cognitive impairment must be taken into consideration when evaluating function (Rosenberg et al, 2009). However, during the literature research no instrument was found to include all relevant ADL areas and existing instruments lacked validity and reliability (Sikkes et al, 2009, Demers et al, 2000.…”
Section: Assessment Instruments and Methodsmentioning
confidence: 99%